2019
DOI: 10.1111/asj.13221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of star anise (Illicium verum Hook.f.) essential oil on nutrient and energy utilization of laying hens

Abstract: An experiment using 96 Hy‐Line brown laying hens at 29 weeks of age that were randomly allocated to four treatments with eight replicates was conducted to assess the effects of star anise (Illicium verum Hook.f.) oil (SAO) on nutrient and energy utilization. Dietary treatments were corn–soybean meal‐based diets supplemented with 0, 200, 400, and 600 mg/kg SAO. The birds were fed the diets for 14 days. The conventional nutrients and amino acids of feed and excreta samples were measured for calculating apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
8
12
0
1
Order By: Relevance
“…Several authors have indicated that the use of EOs stimulates digestive enzyme (such as trypsin and amylase) activity [ 6 ], others a production and induction of a higher secretion of bile acids [ 7 ]. It has been reported that the addition of the various amount of EOs to the laying hen’s diet did not affect dry matter (DM) digestion [ 8 , 9 ]. Radwan Nadia et al [ 10 ] detected that the addition of 0.5% to 1.0% of EOs from thyme, oregano, rosemary, or curcuma to laying hen’s diet did not affect the digestibility of organic matter (OM).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have indicated that the use of EOs stimulates digestive enzyme (such as trypsin and amylase) activity [ 6 ], others a production and induction of a higher secretion of bile acids [ 7 ]. It has been reported that the addition of the various amount of EOs to the laying hen’s diet did not affect dry matter (DM) digestion [ 8 , 9 ]. Radwan Nadia et al [ 10 ] detected that the addition of 0.5% to 1.0% of EOs from thyme, oregano, rosemary, or curcuma to laying hen’s diet did not affect the digestibility of organic matter (OM).…”
Section: Introductionmentioning
confidence: 99%
“…Radwan Nadia et al [ 10 ] detected that the addition of 0.5% to 1.0% of EOs from thyme, oregano, rosemary, or curcuma to laying hen’s diet did not affect the digestibility of organic matter (OM). Yu et al [ 9 ] stated that adding different doses of anise oil (200, 400, and 600 mg/kg) increased the digestibility of OM in laying hens. Although it has been determined in some studies that the addition of EOs increased digestibility of crude protein (CP) in laying hens [ 8 , 9 ], whereas in another research no effect was found [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts, such as Ginkgo biloba leaves (60 g/kg) and extract (0.8 g/kg), were reported to improve the nutrient utilization of broiler chickens in a dose-dependent manner (Ren et al, 2018), and star anise (Illicium verum Hook.f.) essential oil was found to increase the nutrient and energy utilization of Hy-Line brown laying hens (Yu et al, 2019). Plant supplementation experiments using plant extract (200 mg/kg, a blend of oregano, cinnamon and pepper essential oil) and Labiatae extract (5000, a hydroalcoholic extract from sage, thyme and rosemary leaves) increased the ileal digestibility of DM and starch in broiler chicks (Garcia et al, 2007;Hernandez et al, 2004).…”
Section: The Effect Of Ive or Ele On Nutrient Availabilitymentioning
confidence: 98%
“…Antibiotic substitutes, especially plant extracts, have become a research hotspot because of their advantages of promoting growth, antioxidation and environmental friendliness. The Illicium verum oil in feed from 200 to 600 mg/kg was reported to increase feed intake and the feed conversion rate in laying hens (Yu et al, 2019), and 0.5% Eucommia ulmoides extract was found to improve overall growth performance and decrease diarrhoea in weanling piglets (Peng et al, 2019). However, the effect of Illicium verum and Eucommia ulmoides leaf extracts on the nutrient digestion and absorption of Duroc ×Landrace × Yorkshire piglets (DLY) and Chinese Licha-black piglets (LCB) are not clear.…”
Section: Introductionmentioning
confidence: 99%